STUDENT UNDERSTANDING OF THE EFFECTIVENESS OF THE MBKM PROGRAM: A CASE STUDY IN THE MECHANICAL ENGINEERING CLUSTER OF FT UNJ - Tri Bambang AK; Rani Anggrainy; Eko Arif Syaefuddin; Ifaturohiyah Yusuf; Hari Din Nugraha (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2023)
This study aims to evaluate student perceptions of the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Program in the Mechanical Engineering cluster of Jakarta State University. The survey was conducted to collect data from students who are active in the MBKM Program. The data is then analyzed to identify perceptions of the benefits, challenges, and effectiveness of the program. The results showed that the majority of students had an adequate understanding of MBKM and sought information through various sources, such as social media, mass media, and the official website of the Ministry of Education and Culture (Kemdikbud). The Internship/Work Practice Program (MSIB) is the most dominant, and the majority of students benefit positively from MBKM in developing academic skills and learning experiences. Students also reported improvements in hard skills and soft skills. Although some aspects of the program implementation are progressing, the findings point to the need for improvement, especially related to student regulations. Students feel the need to improve good regulations related to the conversion of MBKM program courses. This research contributes to the improvement of the continued development of the MBKM Program in universities